STRATEGI PENGHINDARAN PAJAK PERUSAHAAN SEBELUM DAN SELAMA MASA PANDEMI - Angelina Angelina; Margaretha Margaretha; Rivan Budiman; Septian Bayu Kristanto; Hartoni Hartoni (Jurnal Akuntansi Kontemporer, 2022)
Research Purposes. This research aims to provide empirical evidence of corporate tax avoidance strategies before and during the COVID-19 pandemic. The tax avoidance strategy predicts from three following factors: thin capitalization, profitability, and company size.